2019
DOI: 10.1002/jmor.21070
|View full text |Cite
|
Sign up to set email alerts
|

Cranial suture biomechanics in Metoposaurus krasiejowensis (Temnospondyli, Stereospondyli) from the upper Triassic of Poland

Abstract: Cranial sutures connect adjacent bones of the skull and play an important role in the absorption of stresses that may occur during different activities. The Late Triassic temnospondyl amphibian Metoposaurus krasiejowensis has been extensively studied over the years in terms of skull biomechanics, but without a detailed description of the function of cranial sutures. In the present study, 34 thin sections of cranial sutures were examined in order to determine their histovariability and interpret their biomechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…In general, the growth of Metoposaurus krasiejowensis consists of primary cortex built up of parallel-fibered bone, and sometimes even incipient fibrolamellar bone (Konietzko-Meier & Sander, 2013), which might be exclusively deposited in juvenile individuals (Konietzko-Meier & Sander, 2013). There is also a rich data set published on dermal bones in order to infer information about feeding ecology based on biomechanical reconstruction of metoposaurid skull (Gruntmejer, Konietzko-Meier & Bodzioch, 2016;Gruntmejer et al, 2019a;Gruntmejer et al, 2019b;Konietzko-Meier et al, 2018). Analyzes of vertebrae helped to establish histological ontogenetic stages, a method which allows a relative determination of individual age, based on various histological and microstructural characters of vertebrae, when the classical growth cycles are not developed (Konietzko-Meier, Bodzioch & Sander, 2012) and showed the variability between different temnospondyl groups which may be taxonomically important (Konietzko-Meier, Danto & Gądek, 2014).…”
Section: General Temnospondyl Osteohistologymentioning
confidence: 99%
“…In general, the growth of Metoposaurus krasiejowensis consists of primary cortex built up of parallel-fibered bone, and sometimes even incipient fibrolamellar bone (Konietzko-Meier & Sander, 2013), which might be exclusively deposited in juvenile individuals (Konietzko-Meier & Sander, 2013). There is also a rich data set published on dermal bones in order to infer information about feeding ecology based on biomechanical reconstruction of metoposaurid skull (Gruntmejer, Konietzko-Meier & Bodzioch, 2016;Gruntmejer et al, 2019a;Gruntmejer et al, 2019b;Konietzko-Meier et al, 2018). Analyzes of vertebrae helped to establish histological ontogenetic stages, a method which allows a relative determination of individual age, based on various histological and microstructural characters of vertebrae, when the classical growth cycles are not developed (Konietzko-Meier, Bodzioch & Sander, 2012) and showed the variability between different temnospondyl groups which may be taxonomically important (Konietzko-Meier, Danto & Gądek, 2014).…”
Section: General Temnospondyl Osteohistologymentioning
confidence: 99%
“…The presence of well-mineralised and dense bundles in these areas suggests a strong skeletal muscle attachment of the skull to the vertebral column (Gruntmejer, Konietzko-Meier & Bodzioch, 2016). Moreover, numerous clusters of short Sharpey's fibres occur at sutural edges between adjacent bones (Gruntmejer et al, 2019b). Their presence along the lateral edges of dermal bones refers to the occurrence of collagen fibres within the sutural morphospace which bridged adjacent bones and increased the connections between them (Rafferty & Herring, 1999).…”
Section: Sharpey's Fibresmentioning
confidence: 99%
“…Metoposaurids were cosmopolitan temnospondyls in freshwater Sharpey's fibres shows that the skull was a robust structure which enabled the animal to bite actively on prey. Computational simulation of the skull of Metoposaurus krasiejowensis using FEA (Fortuny, Marcé-Nogué & Konietzko-Meier, 2017) and histological analysis of cranial sutures (Gruntmejer, 2012;Gruntmejer et al, 2019b) have documented that metoposaurids specialised in direct biting during ambush and active hunting. Moreover, previous studies which focused on skull biomechanics in Metoposaurus krasiejowensis, had already shown that histology and the computed Finite Elements (FE) method were not flawless research techniques.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations